Sequence Analysis of Lysozyme C from the Scorpion Mesobuthus Eupeus Venom Glands Using Semi-Nested RT-PCR - Baradaran, M (Kowsar, 2011)
BACKGROUND: Lysozyme is an antimicrobial protein widely distributed among eukaryotes and prokaryotes and take part in protecting microbial infection. Here, we amplified cDNA of MesoLys-C, a c-type lysozyme from the most common scorpion in Khuzestan Province, Southern Iran. METHODS: Scorpions of Mesobuthus eupeus were collected from the Khuzestan Province. Using RNXTM solution, the total RNA was extracted from the twenty separated venom glands. cDNA was synthesized with extracted total RNA as template and modified oligo(dT) as primer. In order to amplify cDNA encoding a lysozyme C, semi-nested RT-PCR was done with the specific primers. Follow amplification, the fragment was sequenced. RESULTS: Sequence determination of amplified fragment revealed that MesoLys-C cDNA had 438 bp, encoding for 144 aa residues peptide with molecular weight of 16.702 kDa and theoretical pI of 7.54. A putative 22-aminoacids signal peptide was identified. MesoLys-C protein was composed of one domain belonged to c-type lysosyme/ alphalactalbumin. CONCLUSION: Multiple alignment of MesoLys-C protein with the related cDNA sequences from various organisms by ClustalW program revealed that some of the conserved residues of other c-type lysosymes were also seen in MesoLys-C. However, the comparison suggested that Mesobuthus eupeus of Khuzestan and east Mediterranean Mesobuthus eupeus belonged to different subspecies.